Sex-biased gene expression and evolution of candidate reproductive transcripts in adult stages of salmon lice (Lepeophtheirus salmonis) - Dylan R. Michaud; Jordan D. Poley; Mark D. Fast (Canadian Science Publishing, 2019)
The salmon louse Lepeophtheirus salmonis (Krøyer 1837) displays numerous sexually dimorphic characteristics. Insights into their underlying molecular components have only recently been explored, which serve to better understand both the basic biology of the louse, associated impacts on drug sensitivity, and evolution of resistance. Expression of 16 L. salmonis genes putatively involved in sexual dimorphism and reproduction were used to determine differences between sexes and better understand responses to mating using RT-qPCR of pre-adult and adult lice. Analysis of these genes revealed the dynamic nature of sex-biased expression across stages. However, female reception of a spermatophore did not appear to impact the expression of these particular genes. Furthermore six of these transcripts and 84 others identified previously in a large-scale louse transcriptomics experiment were used to estimate differences in evolutionary rates and codon-usage bias of sex-related genes using phylogenetic analysis by maximum likelihood (PAML) and codonW. Results suggest male-biased genes are evolving at significantly greater rates than female-biased and unbiased genes as evidenced by higher rates of non-synonymous substitutions and lower codon-usage bias in these genes. These analyses expand our understanding of interactions of sex-biased expression across the pre-adult and adult life stages and provide foundations for better understanding evolutionary differences in sex-biased genes of L. salmonis.